(untitled) (Carte Romanze. Rivista di Filologia e Linguistica Romanze dalle Origini al Rinascimento, 2014)
Nel saggio descrivo le tracce di materiale proveniente dalla tradizione orientale nel canzoniere provenzale C, attraverso un’analisi delle serie e della varia lectio, prima nella sezione di Giraut de Borneil, e poi in quelle di altri autori. In conclusione propongo due ipotesi ricostruttive: la prima riconduce le tracce di tale materiale a un livello alto nello stemma della tradizione manoscritta trobadorica; la seconda suggerisce l’arrivo in Provenza dall’Italia di materiale manoscritto già strutturato, con una fisionomia simile a Da/IK. The work describes the traces of written materials coming from the Eastern trobadoric tradition into the chansonnier C. It analyses both the disposition of the texts in the manuscript and the varia lectio, starting from the authorial section of Giraut de Borneil and then approaching the sections of other authors. The proposed results lead to two hypotheses: the first one brings back the traces of Eastern materials to an ancient initial moment in the trobadoric tradition; the second one suggests that an already organised manuscript materials (similar to our manuscripts DaIK) arrived from Italy into the regions of Southern France.